Integrating Psychedelics into Groupwork: A Culturally Responsive Model for the Counseling Profession - Isaac Burt (MDPI AG, 2024)
Psychedelics, combined with talk therapy, indicate promise with challenging clients, such as those struggling with PTSD. Furthermore, groupwork, with the emphasis on social connections, can be an effective modality. There appears, however, little movement with integrating psychedelics with professional counseling and even less in groupwork. Societal perceptions of psychedelics and the concern of practicing outside one's scope may cause practitioners to hesitate. This article provides a brief overview for the lack of progression in implementing psychedelics in group counseling. I explain what potentially inhibits the utilization of psychedelics, then offer a resolution to these issues by advocating for a psychedelic-assisted groupwork (PAG) model. The argument is that psychedelic approaches can be an innovative and transformative method for group facilitators. I conclude with an overview depicting what a PAG with an interdisciplinary team could entail, including recruitment, screening, selection, therapeutic processes, and termination.